Plasticized cellulose ester compositions having improved weatherability and articles formed therefrom
By using plastic -added cellulose ester composition, including cellulose, lipoplasty plasticizers, and benzopyrene ultraviolet absorbers, the floor materials have been solved in the aspects of processability, weather resistance, and ultraviolet transmission rate. It is equivalent to the performance as Pigvlide flooring while maintaining the characteristics of environmental friendship.
Patent Information
- Application Number
- CN202080070906.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-10
- Filing Date
- 2020-10-08
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-10-08
AI Technical Summary
In floor applications, existing cellulose ester materials are difficult to replace traditional polyvinyl chloride materials due to problems such as difficult processing, poor weather resistance, poor UV transmittance, and flammability.
The plasticized cellulose composition is used. The composition contains at least one cellulose ester, a lipid plasticizer system, and benzoline ultraviolet absorbers to improve the processing and weather resistance of the material.
It realizes the comparable processability, weather resistance, ultraviolet transmission rate and flammable properties as the Pigvlochene floor, while maintaining the characteristics of environmental friendship.
Smart Images

Figure BDA0003586300210000121 
Figure BDA0003586300210000141 
Figure BDA0003586300210000142
Abstract
Description
Technical Field
[0001] The present invention generally relates to plasticized cellulose ester compositions and articles formed therefrom. Background Art
[0002] The growth of cellulose esters has increased significantly as the chemical industry and consumers look for environmentally friendly alternatives to certain chemicals. Cellulose esters are plant-based compounds derived from cellulose, a polysaccharide found in wood, plants, and plant products such as cotton. Cellulose esters have been widely used in various consumer and industrial end-product applications, for example, coatings and coating ingredients, objects - such as eyeglass frames, disposable knives, forks, spoons, plates, cups and straws, toothbrush handles, automotive interiors, camera components, and disposable syringes. Cellulose esters also have intermediate and B2B product uses, usually in the form of fibers, films, sheets, etc. Published research shows that the cellulose esters market is expected to grow from USD 9.27 billion in 2018 to USD 12.43 billion by 2023, at a compound annual growth rate (CAGR) of 6% from 2018 to 2023, and the coatings market is expected to lead this growth.
[0003] Despite this growth, it is recognized in the art that there are challenges in using cellulose esters in certain applications. For example, it is noted in U.S. Published Patent Application No. 2016 / 0068656 that although cellulose esters are generally considered environmentally friendly polymers and are derived from renewable resources such as wood pulp, they have not been widely used in plastic compositions due to processing difficulties. The '656 application goes on to mention the absence of cellulose esters in injection molded articles and asserts that this absence is at least in part due to the narrow temperature window between the melting point and decomposition temperature of cellulose esters. The fact that the production of films and sheets with cellulose esters has historically been limited to standard extrusion and solvent casting methods is also discussed in WO2018017652A1, assigned to the assignee of the present invention.
[0004] As evidenced by the description of WO2018017652A1 cited above and WO2018 / 089591A1, also assigned to the assignee of the present invention, the applicant actively seeks innovations to promote the use of environmentally friendly cellulose esters in various end-use applications. One end-use application of particular interest is so-called "resilient" flooring products, which historically include vinyl sheet flooring, vinyl composite tile, luxury vinyl tile, rubber and linoleum. In this market, polyvinyl chloride was a popular material but has recently become less popular due to environmental concerns. As a result, consumers and product manufacturers seek alternative building materials.
[0005] A particular challenge for materials used in flexible flooring applications is weatherability. During transportation and storage, and especially after installation, flooring materials, especially the top or wear layer of multi-layer flooring materials, may be exposed to significant electromagnetic energy, especially electromagnetic energy in the ultraviolet range (UV) generally between 280nm and 400nm, which is generated by direct sunlight, indirect sunlight through windows, and artificial light such as produced by fluorescent or LED lighting. This exposure can cause discoloration, fading and yellowing of the floor, as well as the formation of visually detectable haze. These phenomena are generally classified as weathering, reduce consumer satisfaction with the product, and inevitably shorten the service life of the product. As an example in the art, U.S. Patent No. 6,572,956 describes a weather-resistant multi-layer resin article and a method for preparing the same.
[0006] In addition to weatherability, flooring products must also meet other attributes that are critical to commercial success or may also need to meet governmental standards for use. For example, flooring products must often meet certain fire safety or flammability standards. In addition, especially for multi-layer flooring products, the top or wear layer must remain substantially transparent while still minimizing the transmission of UV energy to other layers, particularly to the bottom layer that may carry a printed design or image (commonly referred to as the print layer), which may be damaged by UV rays.
[0007] Despite advances in the technology, there remains a continuing unmet need for compositions useful in flooring applications that use environmentally friendly materials while exhibiting processability, weatherability, UV transmittance, flammability, and other performance characteristics comparable to, if not exceeding, polyvinyl chloride flooring. Summary of the invention
[0008] In a first aspect, the present invention is directed to a plasticized cellulose ester composition comprising: at least one cellulose ester; a plasticizer system comprising one or more aliphatic plasticizers; and a benzotriazole UV absorber.
[0009] In another aspect, the present invention is directed to a calendered article comprising: at least one cellulose ester; a plasticizer system comprising one or more aliphatic plasticizers; and a benzotriazole UV absorber.
[0010] In yet another aspect, the present invention is directed to a flooring article comprising at least one layer, wherein the layer comprises a plasticized cellulose ester composition comprising: at least one cellulose ester; one or more aliphatic plasticizers; and a benzotriazole UV absorber.
[0011] Other aspects of the invention are as disclosed and claimed herein. DETAILED DESCRIPTION
[0012] For the avoidance of doubt, it is expressly stated that information and descriptions concerning features or elements of one aspect of the present invention are applicable to those features and elements when described in relation to other aspects of the present invention and are relied upon by and support the latter.
[0013] In a first aspect, the present invention relates to a plasticized cellulose ester composition. The plasticized cellulose ester composition of this aspect of the invention comprises: at least one cellulose ester; a plasticizer system comprising one or more aliphatic plasticizers; and a benzotriazole ultraviolet light absorber.
[0014] As used herein, the term "aliphatic" used to describe plasticizers refers to compounds having carbon atoms that form straight chains, open chains, or rings, but do not have carbon bonds that interact with each other as aromatic rings. Non-limiting examples of aliphatic plasticizers suitable for use in the present invention include: bis(2-ethylhexyl) adipate (DOA); dioctyl adipate, triethylene glycol bis(2-ethylhexanoate) (TEG-EH), dihexyl azelate, triethyl citrate, triethyl acetyl citrate, triacetin, tripropionin, tributyrin, and polymerized adipates, such as those commercially available under the following trade names: Admex 523, Admex 525, Admex 6995, Admex 761, Admex 910-001, Admex 6187, Admex 770, and Admex 760, and combinations thereof. In one or more embodiments, the aliphatic plasticizer is selected from the group consisting of aliphatic esters, such as triethylene glycol bis (2-ethylhexanoate) (TEG-EH), bis (2-ethylhexyl) adipate (DOA), dioctyl adipate and combinations thereof. In one or more embodiments, the aliphatic plasticizer is triethylene glycol bis (2-ethylhexanoate) (TEG-EH). The term "system" used to describe a plasticizer system is intended to include a single plasticizer as well as a combination of two or more plasticizers.
[0015] An important feature of the present invention is that when compared with aromatic plasticizers, aliphatic plasticizers have unexpected synergistic effects on the weatherability of compositions and articles when used in combination with benzotriazole ultraviolet light absorbers. Therefore, in one or more embodiments, based on the gross weight of the plasticizer system, the plasticizer system comprises an aliphatic plasticizer of the following content: at least 60wt%, or at least 65wt%, or at least 70wt%, or at least 75wt%, or at least 80wt%, or at least 85wt%, or at least 90wt%, or at least 92wt%, or at least 94wt%, or at least 96wt%, or at least 98wt%, or 100wt%. In one or more embodiments, the plasticizer system is a plasticizer system consisting of one or more aliphatic plasticizers or consisting essentially of one or more aliphatic plasticizers. In one or more embodiments, the composition of the present invention is substantially free of aromatic plasticizers. As used herein, the term "aromatic" used to describe plasticizers refers to compounds containing a planar unsaturated carbon atom ring that is stabilized by the interaction of the bonds (sometimes referred to as resonant bonds) that form the ring. Examples of aromatic plasticizers include: aromatic diesters, such as tris (2-ethylhexyl) trimellitate (TOTM), phosphate esters, such as resorcinol bis (diphenyl phosphate) (RDP), bisphenol A bis (diphenyl phosphate) (BDP), bis-xylyl phosphate (RXP), triphenyl phosphate, aryl phosphate (SOL-DP), tricresyl phosphate, toluene diphenyl phosphate, 2-ethylhexyl diphenyl phosphate and phthalate plasticizers, such as dioctyl phthalate, dibutyl phthalate.
[0016] In one or more embodiments, the plasticized cellulose ester composition comprises 5 wt%-35 wt% or 10 wt%-30 wt% of the plasticizer system, based on the total weight of the composition.
[0017] The plasticized cellulose ester composition of the present invention comprises at least one cellulose ester. Cellulose esters are generally defined as cellulose esters comprising one or more carboxylic acids, such as described in U.S. Patent No. 5,929,229 assigned to the assignee of the present invention, the contents and disclosure of which are incorporated herein by reference. Non-limiting examples of cellulose esters include: cellulose acetate, cellulose propionate, cellulose butyrate, so-called mixed acid esters such as cellulose acetate propionate and cellulose acetate butyrate, and combinations thereof. In one or more embodiments, at least one cellulose ester is selected from: cellulose acetate, cellulose acetate propionate, or cellulose acetate butyrate, and combinations thereof. In one or more embodiments, the cellulose ester is cellulose acetate. In one or more embodiments, at least one cellulose ester is cellulose acetate propionate. In one or more embodiments, at least one cellulose ester is cellulose acetate butyrate. In one or more embodiments, at least one cellulose ester is a combination of cellulose acetate propionate and cellulose acetate butyrate.
[0018] In one or more embodiments, the amount of at least one cellulose ester in the plasticized cellulose ester composition is 25 wt%-99 wt%, or 35 wt%-95 wt%, or 45 wt%-95 wt%, all based on the total weight of the plasticized cellulose ester composition.
[0019] The cellulose esters of the present invention can be characterized using one or more characteristics. For example, in one or more embodiments, the number average molecular weight ("Mn") of the cellulose ester can be in the range of 20,000 Da to 100,000 Da. In one or more embodiments, the Mn of the cellulose ester is in the range of about 20,000 Da to about 80,000 Da.
[0020] In one or more embodiments, the solution drop ball viscosity of the cellulose ester may be 2-30, or 4-25, or 5-20 seconds, measured according to ASTM D817.
[0021] In one or more embodiments, the cellulose ester may have a degree of substitution of hydroxyl substituents (DSOH) of 0.1-1.0, or a degree of substitution of acetyl groups (DSAC) of 0.1-0.8. As a brief background, DSOH and DSAC are measures of the degree of esterification of a given cellulose ester. Each anhydroglucose unit of cellulose has three hydroxyl groups, located on the C2, C3, and C6 carbon atoms, which can be esterified to varying degrees and in varying proportions by various acyl groups, and the type of cellulose ester formed depends on the functionalization of the hydroxyl groups. For example, for cellulose triacetate, in which substantially all of the hydroxyl groups of the cellulose are functionalized with acetyl groups, the degree of substitution of acetyl groups ("DSAC") may be about 2.90, and the degree of substitution of hydroxyl groups ("DSOH") may be about 0.10. The DSAC of cellulose diacetate is about 2.5, and the DSOH is about 0.5.
[0022] In one or more embodiments, the glass transition temperature (T g ) can be from 50°C to 150°C, or from 70°C to 120°C, or not more than 160°C.
[0023] In one or more embodiments, the cellulose ester may have the following percentage crystallinity: less than 20%, or less than 15%, or less than 10%, or less than 5%, or 5% to 10%, or 5% to 15%, or 5% to 20%, or 10% to about 20%. Crystallinity is described herein using the second thermal cycle, and in the context of the present invention, the crystallinity is measured from the second thermal cycle according to ASTM D3418 and assuming that the melting enthalpy of the cellulose ester is 14 cal / g. In this method, the amount of crystallinity is measured under a specified heating history, more specifically under the "second cycle" cooling and heating in DSC according to ASTM D3418. In this method, the sample is first heated to above its melting temperature in the DSC to eliminate any previous crystallinity (i.e., the "first thermal cycle"). Next, the sample is cooled to T at a rate of 20°C per minute. g Following this, it is then heated again at the same rate to above the melting temperature ("second thermal cycle"). During this cooling and second heating, the material will recrystallize to some extent, and this amount of crystallization is measured in the scan as the melting enthalpy at the melting temperature.
[0024] The compositions of the present invention include benzotriazole UV absorbers. Benzotriazole UV absorbers are a class of compounds and compound derivatives containing a benzotriazole moiety that absorb electromagnetic radiation in the ultraviolet range. Benzotriazole UV absorbers and methods for their preparation are described, for example, in U.S. Pat. No. 3,629,191, the contents and disclosure of which are incorporated herein by reference. Benzotriazole UV absorbers are commercially available, for example, from BASF Corporation under the trade name TINUVIN TM CYASORB TMExamples of benzotriazole ultraviolet absorbers include, but are not limited to, benzotriazole (BTA), 2-(2-hydroxy-5-tert-octylphenyl)-benzotriazole, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(3",4",5",6"-tetrahydrophthalimide 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-(2-octyloxycarbonylethyl)-phenyl)-5-chlorobenzotriazole, and 2-(2'-hydroxy-3'-(1-methyl-1-phenylethyl))-5'-(1,1,3,3-tetramethylbutyl)-phenyl)benzotriazole, and combinations thereof.
[0025] In one or more embodiments of the present invention, the benzotriazole UV absorber is present in an amount of 0.05wt% to 1.5wt%, or 0.25wt% to 1wt%, or at least 0.25wt%, based on the total weight of the composition. However, it will be appreciated by those skilled in the art that less amounts of benzotriazole UV absorbers may be used in the present invention, particularly when other non-benzotriazole UV absorbers are included.
[0026] As discussed above, an important feature of the present invention is that aliphatic plasticizers (especially compared to aromatic plasticizers) have an unexpected synergistic effect on the [long-term] weatherability of compositions and articles when used in combination with benzotriazole UV absorbers. This unexpected synergistic effect can be demonstrated by measurement of one or more tests known in the art for demonstrating and quantitatively measuring the weatherability of compositions and related articles, such as typically demonstrated by color change. In one or more embodiments, the present invention can exhibit one or more of the following: (a) a b* color measurement change (Δb) of no more than 1.25, or no more than 1.0, or no more than 0.8 units as measured according to ASTM E1164-12 when subjected to 3,147 hours of accelerated weathering according to ASTM D-4674 Method IV; (b) a total color change (ΔE) of no more than 0.5, or no more than 0.4, or no more than 0.3 units as measured according to ASTM D2244 when subjected to 3,147 hours of accelerated weathering according to ASTM D-4674 Method IV; and (c) a yellowness index change (ΔY) of no more than 2.0, or no more than 1.75, or no more than 1.5 units as measured according to ASTM E313 when subjected to 3,147 hours of accelerated weathering according to ASTM D-4674 Method IV. In one or more embodiments, the present invention can exhibit a b* color measurement change (Δb) of no more than 1.25, or no more than 1.0, or no more than 0.8 units when subjected to 3,147 hours of accelerated weathering according to ASTM D-4674 Method IV, as measured according to ASTM E1164-12. In one or more embodiments, the present invention can exhibit a total color change (ΔE) of no more than 0.5, or no more than 0.4, or no more than 0.3 units when subjected to 3,147 hours of accelerated weathering according to ASTM D-4674 Method IV, as measured according to ASTM D2244. In one or more embodiments, the present invention can exhibit a yellowness index change (ΔY) of no more than 2.0, or no more than 1.75, or no more than 1.5 units when subjected to 3,147 hours of accelerated weathering according to ASTM D-4674 Method IV, as measured according to ASTM E313.In one or more embodiments, the present invention may exhibit one or more of the following: (a) a b* color measurement change (Δb) of no more than 0.3, or no more than 0.25, or no more than 0.2 units when subjected to 1,647 hours of accelerated weathering according to ASTM D-4674 Method IV as measured according to ASTM E1164-12; (b) a total color change (ΔE) of no more than 0.3, or no more than 0.25, or no more than 0.2 units when subjected to 1,647 hours of accelerated weathering according to ASTM D-4674 Method IV as measured according to ASTM D2244; and (c) a yellowness index change (ΔY) of no more than 0.5, or no more than 0.45, or no more than 0.4 units when subjected to 1,647 hours of accelerated weathering according to ASTM D-4674 Method IV as measured according to ASTM E313. In one or more embodiments, the present invention may exhibit two or more, or three or more, or four of the Δb, ΔE, and ΔY characteristics described above.
[0027] In addition to the above, when subjected to 3,147 hours of accelerated aging according to ASTM D-4674 Method IV, the present invention can exhibit in one or more embodiments a change in haze (ΔH) of no more than 2.8, or no more than 2.7, or no more than 2.6 units as measured according to ASTM D1003-13. In addition to the above, when subjected to 1,647 hours of accelerated aging according to ASTM D-4674 Method IV, the present invention can exhibit in one or more embodiments a change in haze (ΔH) of no more than 0.5, or no more than 0.4, or no more than 0.3 units as measured according to ASTM D1003-13.
[0028] In addition to the above, the present invention may exhibit a UV transmission percentage of no more than 2%, or no more than 1%, or no more than 0.5%, or no more than 0.25%, or no more than 0.10%, or no more than 0.05%, or no more than 0.04%, or no more than 0.03%, or no more than 0.02% between wavelengths of 300 nm and 350 nm (for a film of 20 mil thickness).
[0029] Those of ordinary skill in the art will appreciate that the above characteristics are typically measured on samples in sheet or film form. Therefore, the compositions of the present invention exhibit these characteristics when formed into films or sheets. In one or more embodiments, the compositions of the present invention exhibit these characteristics when formed into films or sheets suitable for use as flooring product layers. The thickness of the films or sheets suitable for use as flooring product layers will vary depending on the type of flooring product, and if multi-layered, depending on the location and function of the particular layer. For laminated structures, the sheet thickness is typically between 3 mils and 500 mils, or for the top wear layer, the sheet thickness is typically between 1 mil and 40 mils.
[0030] The composition of the present invention may also include one or more processing aids, impact modifiers and roll release agents. In one or more embodiments, the plasticized cellulose ester composition of the present invention may include at least one roll release agent. Suitable roll release agents are known in the art and are described, for example, in U.S. Patent No. 6,551,688, the contents and disclosure of which are incorporated herein by reference. Examples of suitable roll release agents include, but are not limited to, lubricants, waxes such as amide waxes, fatty acids, fatty acid esters, fatty acid salts, saponified fatty acid salts and combinations thereof. Examples of fatty acid esters include esters of montanic acid. In one or more embodiments, the roll release agent is a fatty acid ester selected from the group consisting of butanediol esters of montanic acid, glycerol esters of montanic acid, pentaerythritol esters of montanic acid and combinations thereof.
[0031] When included in the present invention, at least one roller release agent is generally present in an amount of 0.1 wt% to about 2.0 wt%, based on the total weight of the composition. In one or more embodiments, at least one roller release agent is present in an amount of 0.1 wt% to 1.0 wt%, based on the total weight of the composition. In one or more embodiments, at least one roller release agent is present in an amount of 0.1 wt% to 0.5 wt%, based on the total weight of the composition. In one or more embodiments, at least one roller release agent is present in an amount of 0.5 wt% to 1.0 wt%, based on the total weight of the composition. In one or more embodiments, at least one roller release agent is present in an amount of 1.0 wt% to 2.0 wt%, based on the total weight of the composition. In one or more embodiments, at least one roller release agent is present in an amount of 1.5 wt% to 2.0 wt%, based on the total weight of the composition.
[0032] The present invention may also include at least one processing aid. Processing aids may, for example, improve the texture and "fusion" of the melt, increase melt strength, reduce composition melting time, reduce total processing time, and aid in demolding the metal from the calender rolls. Processing aids are known in the art and may be derived from, for example, acrylic acid and acrylic acid copolymers, although processing aids based on styrene, carbonates, polyesters, other olefins, and siloxanes are known and commercially available. Suitable processing aids are commercially available and include, but are not limited to, Paraliod available from Dow. TM K-125; available from Kaneka Corporation PA-20, PA-610, B622, MR01, and MP90; and Ecdel available from Eastman Chemical Company TMIn one or more embodiments, at least one processing aid comprises one or more of an acrylic polymer, an acrylic copolymer, a styrene polymer, a carbonate polymer, a polyester polymer, an olefin polymer, and a siloxane polymer. In one or more embodiments, at least one processing aid is selected from the group consisting of an acrylic polymer or an acrylic copolymer. In one embodiment, the processing aid comprises Acrylic processing aid.
[0033] The amount of at least one processing aid present in the present invention can vary depending on the type of processing aid and its molecular weight and viscosity, the other components of the composition, and the end-use application of the composition. In one or more embodiments, based on the total weight of the composition, at least one processing aid is present in an amount of 0wt% to about 3.0wt%. In one or more embodiments, based on the total weight of the composition, at least one processing aid is present in an amount of 0.1wt% to 6.0wt%. In one or more embodiments, based on the total weight of the composition, at least one processing aid is present in an amount of 0.5wt% to 6.0wt%. In one or more embodiments, based on the total weight of the composition, the processing aid is present in an amount of 0.5wt% to 3.0wt%.
[0034] The present invention may also include at least one impact modifier. Examples of impact modifiers include core-shell polymers based on acrylics, including acrylic polymers, methacrylate butadiene styrene (MBS) polymers, silicone-acrylic polymers, and combinations thereof. Other suitable impact modifiers include acrylonitrile-butadiene-styrene (ABS), ethylene-vinyl acetate copolymers, chlorinated polyethylene, ethylene copolymers, and combinations thereof. At least one impact modifier, if present, is typically present in an amount of 1 wt % to about 20 wt %, based on the total weight of the composition.
[0035] The composition of the present invention may also contain one or more other ingredients or components, for example: fillers such as calcium carbonate, flame retardants, lubricants, pigments, dispersing aids, biocides, antistatic agents, water repellent additives, rodenticides, dyes, colorants, etc.
[0036] In one or more embodiments, the compositions of the present invention are suitable for or capable of forming a calendered article, such as a sheet or film. Thus, in one aspect, the present invention relates to a calendered article comprising or formed from a plasticized cellulose ester composition comprising: at least one cellulose ester; a plasticizer system comprising one or more aliphatic plasticizers; and a benzotriazole ultraviolet light absorber. As previously stated, the information and descriptions set forth with respect to the features and elements of the plasticized cellulose ester composition aspect or other aspects of the present invention are intended to be applicable to and fully support the calendered article aspect.
[0037] By using the phrase "calendered article", the present invention is intended to describe an article, such as a film or sheet, formed from a molten polymer using a calendering process, wherein the molten polymer is forced through the nip of counter-rotating rollers to form a film or sheet, which is gradually extruded downward to a final thickness by optionally passing through additional rollers having similar counter-rotating devices (the roller device is generally referred to as a "stack"); the film or sheet is subjected to additional processing, such as stretching, annealing, cutting, etc., and then the formed article is wound on a winder. Calendering and calendered articles as used herein are described in more detail in U.S. Published Patent Application No. 2019 / 0256674 assigned to the assignee of the present invention, the contents and disclosure of which are incorporated herein by reference.
[0038] In one or more of these embodiments, the temperature of the -1 The melt viscosity of the plasticized cellulose ester composition is from 1000 poise to 5000 poise, or from 2000 poise to 5000 poise at a shear rate of 1.5 %. In one or more of these embodiments, the plasticized cellulose ester composition of the present invention can be calendered within the following temperature range: the glass transition temperature of the cellulose ester of the composition minus 20°C to the glass transition temperature of the cellulose ester of the composition plus 50°C. In view of these embodiments, one aspect of the present invention is a calendered article formed from the plasticized cellulose ester composition of the present invention, particularly wherein the calendered article is a film, sheet or layer of a multilayer article.
[0039] Although the foregoing aspects of the present invention describe the use of the plasticized cellulose ester composition of the present invention in the field of calendering and calendered products, it will be understood by those of ordinary skill in the art that the composition of the present invention can also be used to form articles by other known methods, such as extrusion, injection molding, blow molding, additive manufacturing (3D printing), profile extrusion, blown film, multilayer film, sheet lamination, etc.
[0040] The plasticized cellulose ester composition of the present invention can be used to form flooring products, calendered flooring products, or more particularly to form flooring product layers or calendered layers of flooring products. Therefore, in another aspect, the present invention relates to a flooring product. The flooring product of this aspect of the present invention includes at least one layer. In one or more embodiments, at least one layer is a calendered layer. In one or more embodiments, at least one layer is formed by the plasticized cellulose ester composition of the present invention. Therefore, at least one layer comprises a plasticized cellulose ester composition, which comprises: at least one cellulose ester; a plasticizer system comprising one or more aliphatic plasticizers; and a benzotriazole ultraviolet absorber. Flooring products considered within the scope of the present invention include, but are not limited to, any material or structure intended to be used as, installed in, or applied to a walking surface or lower surface of a room or building. Non-limiting examples of flooring products include: rolled floors, mortar boards (squares), tiles, thick boards, thin boards, laminates, and similar products that can be installed as, for example, so-called "floating" floors or glued floor assemblies. As previously mentioned, the information and descriptions set forth regarding the features and elements of the plasticized cellulose ester composition aspect or other aspects of the present invention are applicable to and intended to fully support this aspect involving flooring products.
[0041] In one or more embodiments, the flooring article is a resilient flooring article. In one or more embodiments, the resilient flooring article is a multi-layer resilient flooring article or a laminate flooring article. Exemplary multi-layer flooring articles may include, but are not limited to, a top layer or wear layer, a base layer or core layer, and a printable layer or printed layer between the top layer or wear layer and the base layer or core layer. The top layer or wear layer provides scratch resistance and abrasion resistance while also allowing any underlying printed layer design to be visible through the top layer surface, typically with a thickness of between 15 mils and 25 mils. The base layer or core layer provides dimensional stability, typically with a thickness of at least 75 mils. The printable layer may provide visual color and / or design, such as in the form of a geometric pattern or image, typically with a thickness of between 3 mils and 5 mils. Multi-layer flooring articles of the type contemplated herein are generally known in the art, such as described in U.S. Patent No. 8,071,193, the contents and disclosure of which are incorporated herein by reference.
[0042] In one or more embodiments, the flooring article of the present invention can be a multilayer resilient flooring article including a top layer or wear layer, and at least one layer is the top layer or wear layer of the multilayer flooring article. Typically, the top layer or wear layer of the multilayer flooring article is a layer that is significantly exposed to ultraviolet radiation, such as from sunlight or indoor fluorescent or LED lighting. Therefore, in one or more embodiments, at least one layer is the top layer or wear layer of the multilayer flooring article. However, as described above, the multilayer floor may also include a base layer or core layer, and a printable layer between the top layer or wear layer and the base layer or core layer, and it should be understood that layers other than the top layer can benefit from the unexpectedly excellent weather resistance achieved by the present invention. Therefore, in one or more embodiments, the present invention is a multilayer flooring article, which includes: a top layer or wear layer, a base layer or core layer, and a printable layer between the top layer or wear layer and the base layer or core layer, and at least one layer is a printable layer of the multilayer flooring article. Similarly, in one or more embodiments, the present invention can be a multi-layer flooring product, which includes: a top layer or wear layer, a base layer or core layer, and a printable layer between the top layer or wear layer and the base layer or core layer, and at least one layer is a base layer or core layer of the multi-layer flooring product. In one or more embodiments, at least one layer is a calendered layer or calendered sheet or calendered film.
[0043] Although the following examples are provided to specifically and in detail illustrate the many aspects and advantages of the present invention, they should not be construed as limiting the scope thereof in any way. Those skilled in the art will readily appreciate changes, modifications and variations that do not depart from the spirit of the present invention.
[0044] In order to prove the present invention, the sample of the present composition is formulated to include cellulose ester, aliphatic plasticizer and benzotriazole ultraviolet light absorber. These are marked as 156-2, 156-3 and 156-4 in the following table 1. Two types of control compositions have also been prepared for comparison. One group of control compositions includes cellulose ester and aromatic plasticizer: a sample in the group does not include benzotriazole ultraviolet light absorber (sample 156-5), and four samples in the group include different amounts of benzotriazole ultraviolet light absorber (sample 156-6 to 156-9). Another kind of control material (sample 156-1) includes cellulose ester and aliphatic plasticizer, does not contain benzotriazole ultraviolet light absorber. The component amount based on the total weight of the composition is shown in Table 1 with weight percentage.
[0045] Table 1
[0046]
[0047] With respect to the components in Table 1: CAP 482 is a high viscosity cellulose acetate propionate available from Eastman Chemical Company with a solution drop ball viscosity of 20 seconds measured in accordance with ASTM D817; TEG2EH is triethylene glycol bis(2-ethylhexanoate), an aliphatic plasticizer available from Eastman Chemical Company; RDP is resorcinol bis(diphenyl phosphate), an aromatic plasticizer / flame retardant available from ICL-IP as Fyrofex TM SOL-DP is a proprietary aromatic plasticizer / flame retardant also provided by ICL-IP, with a melting point range of 101°C to 108°C and a plasticizing effect at processing temperatures; Cyasorb TM 5411 is 2-(2-hydroxy-5-tert-octylphenyl)-benzotriazole, a benzotriazole UV absorber sold by Solvay.
[0048] To form each of the above formulations, the components were mixed on a Leistritz 18 mm multi-zone twin screw extruder with zone temperatures varying from 90°C for the feed zone temperature to 220°C at the vent and die. The screw speed was a medium shear design and varied between 500-575 rpm. Films of 20 mil thickness were pressed from each formulation on a Carver press at temperatures of 190°C-200°C and pressures up to 15,000 psi.
[0049] The film samples formed as described above were optically tested according to the following analytical method to establish a baseline value for comparison (t=0), and then accelerated aging was performed using a SolarEye aging device with a UV fluorescent bulb (peak irradiance of 351nm) following ASTM D4674 Method IV. During the test, the sample was placed vertically. The sample was exposed for 3,147 hours, and the optical properties were measured at the intermediate exposure level of 1647 hours and at the end of the exposure time (3147 hours). The ultraviolet absorption of the film sample was also tested by measuring the ultraviolet transmission through the sample.
[0050] Analytical methods
[0051] Weatherability is evaluated and quantitatively measured using optical tests known in the art for measuring color and haze, as is conventional in the art. Color data was obtained using a Hunter Lab UltraScan spectrophotometer (Model 8000) in reflection mode and D65 illuminant* (daylight, world average at noon, ~6500°K correlated color temperature). Color was measured directly to measure L*, a* and b* values, total color change (ΔE*) (ASTM D2244), and yellowness index (Y) (ASTM E313). Haze (H) was measured using a HunterLab UltraScan spectrophotometer (Model 8000) in transmission mode using a D65 illuminant (daylight, world average at noon, 6500°K correlated color temperature), a 10° standard observer, a large area view (1" diameter), and including specular reflection. Haze data was collected according to ASTM D1003. Higher b*, E, and yellowness and haze values correspond to increased color and haze, which is due to exposure to accelerated aging.
[0052] The UV transmission change of 20 mil samples was tested on a PerkinElmer Lambda 850 UV / Vis spectrophotometer. Wavelengths at the shorter wavelength end of the UV region are of particular concern because they have relatively high energy and are more likely to penetrate the wear layer and cause damage to the printed layer. Wavelength scans were collected from 300nm to 350nm using a 1nm data interval and a scan speed of 266.75nm / min. Measurements were made and data was generated in "% Transmission" mode using a beam attenuator. The light sources used were deuterium sources with wavelengths up to 319.2nm wavelength and tungsten halogen sources with wavelengths exceeding 319.2nm. The detection system used a photomultiplier tube, the detector slit width was 2nm, and the detector response was 0.2 seconds.
[0053] The results of the optical and UV absorption tests are listed below in Tables 2 and 3, respectively.
[0054] Table 2
[0055]
[0056]
[0057] Table 3
[0058]
[0059] As shown in Table 2 above, the present invention unexpectedly demonstrated long-term weatherability (measured by color change and haze) superior to all control samples. Particularly surprising was the superior weatherability of the samples containing a benzotriazole UV absorber plus an aliphatic plasticizer plasticizer system (Nos. 156-2, 156-3, and 156-4) when compared to samples containing the same amount of a benzotriazole UV absorber plus an aromatic plasticizer plasticizer system (Nos. 156-6, 156-7, 156-8, and 156-9). Note that sample 156-2 became sufficiently brittle at the end of the exposure period to interfere with optical testing; therefore, the optical test values were not determined (indicated as "ND" in Table 2).
[0060] As shown in Table 3 above, the improved weathering properties demonstrated in Table 2 are achieved without compromising UV absorption properties which are critical to resilient flooring, particularly the top layer or wear layer of a resilient multi-layer floor having a printed layer beneath the wear layer.
[0061] The above description of various embodiments of the present invention has been given for the purpose of illustration and description. It is not intended to be exhaustive or to limit the invention to the precise embodiments disclosed. Many modifications or variations are possible in light of the above teachings. The embodiments discussed are selected and described in order to provide the best illustration of the principles of the invention and its practical application, thereby enabling one of ordinary skill in the art to utilize the invention in various embodiments and with various modifications to suit the particular use contemplated. All such modifications and variations are within the scope of the invention as determined by the appended claims when interpreted in accordance with the scope to which they are fairly, legally and equitably entitled.
Claims
1. A plasticized cellulose ester composition comprising: at least one cellulose ester; a plasticizer system comprising an aliphatic plasticizer; and a benzotriazole ultraviolet light absorber, in, The aliphatic plasticizer is triethylene glycol bis(2-ethylhexanoate) (TEG-EH).
2. The composition according to claim 1, wherein The composition comprises 10 wt% to 35 wt% of the plasticizer system, based on the total weight of the composition.
3. The composition according to claim 2, wherein The composition comprises 15 wt% to 30 wt% of the plasticizer system, based on the total weight of the composition.
4. The composition according to claim 1, wherein The composition includes 0.05 wt % to 1.5 wt % of the benzotriazole ultraviolet absorber based on the total weight of the composition.
5. The composition according to claim 4, wherein The composition includes 0.25 wt % to 1.0 wt % of the benzotriazole ultraviolet absorber based on the total weight of the composition.
6. The composition according to claim 1, wherein The composition also includes one or more of the following: roller release agents, processing aids, impact modifiers, fillers, flame retardants, lubricants, pigments, dispersing aids, biocides, antistatic agents, water repellent additives, rodenticides, dyes, and colorants.
7. The composition according to claim 1, wherein The at least one cellulose ester is selected from the group consisting of cellulose acetate propionate, and cellulose acetate butyrate, and combinations thereof.
8. The composition according to claim 1, wherein The composition, when formed into a film or sheet suitable for use as a layer of a flooring article, exhibits one or more of the following: (a) a change in b* color measurement (Δb) of no more than 1.25 units when subjected to 3,147 hours accelerated weathering according to ASTM D-4674 Method IV as measured according to ASTM E1164-12; (b) a total color change (ΔE) of no more than 0.25 units when subjected to 3,147 hours accelerated weathering according to ASTM D-4674 Method IV as measured according to ASTM D2244; and (c) a change in yellowness index (ΔY) of no more than 2.0 units when subjected to 3,147 hours accelerated weathering according to ASTM D-4674 Method IV as measured according to ASTM E313.
9. The composition according to claim 8, wherein The composition, when formed into a film or sheet suitable for use as a flooring article layer, exhibits a haze change (ΔH) of no more than 2.8 units when measured in accordance with ASTM D1003-13 upon accelerated aging for 3,147 hours in accordance with ASTM D-4674 Method IV.
10. The composition according to claim 8, wherein A film or sheet of the composition exhibits an ultraviolet transmittance of no more than 0.1% at a thickness of 20 mils.
11. A flooring article comprising at least one layer, said layer comprising a plasticized cellulose ester composition comprising: at least one cellulose ester; a plasticizer system comprising an aliphatic plasticizer; and a benzotriazole ultraviolet light absorber, in, The aliphatic plasticizer is triethylene glycol bis(2-ethylhexanoate) (TEG-EH).
12. The flooring article of claim 11, wherein the at least one layer is a top layer or a wear layer of a multi-layer flooring article.
13. The flooring product according to claim 12, wherein: The layer exhibits one or more of the following: (a) a change in b* color measurement (Δb) of no more than 1.25 units when subjected to 3,147 hours of accelerated weathering according to ASTM D-4674 Method IV as measured according to ASTM E1164-12; (b) a total color change (ΔE) of no more than 0.25 units when subjected to 3,147 hours of accelerated weathering according to ASTM D-4674 Method IV as measured according to ASTM D2244; and (c) a change in yellowness index (ΔY) of no more than 2.0 units when subjected to 3,147 hours of accelerated weathering according to ASTM D-4674 Method IV as measured according to ASTM E313.
14. The flooring product according to claim 12, wherein: The layer exhibits a haze change (ΔH) of no more than 2.8 units when subjected to accelerated weathering according to ASTM D-4674 Method IV for 3,147 hours as measured according to ASTM D1003-13.
15. The flooring article of claim 12 wherein the layer exhibits an ultraviolet transmittance of no more than 0.1% at a thickness of 20 mils.
16. The flooring article of claim 11, wherein the at least one layer does not contain an aromatic plasticizer.
17. The flooring article of claim 12, wherein the at least one layer is a calendered film or a calendered sheet.
18. A calendered article comprising a plasticized cellulose ester composition comprising: at least one cellulose ester; a plasticizer system comprising an aliphatic plasticizer; and a benzotriazole ultraviolet light absorber, in, The aliphatic plasticizer is triethylene glycol bis(2-ethylhexanoate) (TEG-EH).
19. The calendered article according to claim 18, wherein the calendered article is a sheet or a film.
Citation Information
Patent Citations
Cellulose ester plastics and methods and articles relating thereto
US20160068656A1
Cellulose ester compositions for calendering
US20190256674A1
UV-absorbing hydroxyphenyl-benzotriazoles
US3629191A
Direct process for the production of cellulose esters
US5929229A
Calendered polyester films or sheets having a haze value of less than five percent
US6551688B2